Petrophysical properties of the Lower Cretaceous formations in the Shaikhan oilfield, northern Iraq - Wria Jihad Jabbar; Srood Farooq Naqshabandi; Falah Khalaf Al-Juboury (Earth Sciences Research Journal)
The current study represents an evaluation of the petrophysical properties in the well Shaikhan-8 for the Garagu, Sarmord and Qamchuqa formations in Shaikhan oilfield, Duhok basin, northern Iraq. The petrophysical evaluation is based on well logs data to delineate the reservoir characteristics. The environmental corrections and petrophysical parameters such as porosity, water saturation, and hydrocarbon saturation are computed and interpreted using Interactive Petrophysics (IP) program. Neutron-density crossplot is used to identify lithological properties. The Qamchuqa Formation in the Shaikhan oilfield consists mainly of dolomite with dolomitic limestone, and the average clay volume is about 13%; while Sarmord Formation composed of limestone and dolomitic limestone, the average clay volume in this formation is about 19%; also the Garagu Formation consists mainly of limestone and dolomitic limestone in addition to sandstone and claystone, the volume of clay in the Garagu Formation is about 20%. Pickett plot method is used to calculate formation water resistivity (Rw), saturation exponent (n) and cementation exponent (m) the values are 0.065ohm, 2, and 2.06 respectively. The porosity ratio (Ø) of the Qamchuqa Formation ranges between 7-15%; this indicates that the lower part of the formation has a poor-fair porosity (7%), while the upper part of the formation has a good porosity (15%). The porosity value decrease toward Sarmord Formation especially in the lower part of the formation, it has a poor porosity (5%), whereas this value reaches to 13% in the upper part of the formation, indicates for fair porosity. Garagu Formation has good porosity, reaches 20% in the lower part, but in the upper part of the formation, this value decreases to 3%. Water saturation (Sw) value which is calculated by Archie equation ranges between 14-33%, while saturation in the flushed zone (Sxo) ranges between 52-73%, these indicate for good movable hydrocarbons are present in the studied interval (840-1320m), and from the total 480m the Early Cretaceous formations in well Shaikhan-8 have 178m pay.